Developing customer relationship management for Golden Partners Management in achieving sustainable performance / Norhayati Mohammad - Mohammad, Norhayati (Faculty of Business and Management, 2005)
This research was conducted to develop customer relationship management (CRM) for Golden Partners Management (GPM) in achieving sustainable performance. The main objective of this research is to highlighted the current practices of customer relationship (CR) and the lack of, also to find out the important of CR either to the organization or to the customers and lastly to see whether there are differences in view towards CR by the organization and also the customers. CRM are importance to be practices because of the competitive marketplace and the changing of customers. Today customers are more slippery; where they keep ask more and more information about products or services. And also they apply for new ways of communications, the communications is CRM. Based on finding, it can be concluded here CRM should be practice because of the benefits it give to the organizations and also to their customers. There lot of benefits if they practice CRM, and to be successful several steps should be followed.